Neuroenhancement and neuroprotection by oral solution citicoline in non-arteritic ischemic optic neuropathy as a model of neurodegeneration: A randomized pilot study - Parisi, Vincenzo; Barbano, Lucilla; Di Renzo, Antonio; Coppola, Gianluca; Ziccardi, Lucia (PloS one, 2019)
To evaluate whether treatment with Citicoline in oral solution (OS-Citicoline) would increase visual function, retinal ganglion cells (RGCs) function, and neural conduction along visual pathways (neuroenhancement), and/or induce preservation of RGCs fibers' loss (neuroprotection) in non-arteritic ischemic optic neuropathy (NAION), a human model of neurodegeneration. Thirty-six patients with NAION and 20 age-matched controls were enrolled. Nineteen NAION patients received 500 mg/day of OS-Citicoline for a 6-month period followed by 3-month of wash-out (NC Group); 17 NAION patients were not treated (NN Group) from baseline to 9 months. In all subjects at baseline, and in NC and NN eyes at 6 and 9 months of follow-up, we assessed Visual Acuity (VA), Pattern Electroretinogram (PERG), Visual Evoked Potentials (VEP), retinal nerve fiber layer thickness (RNFL-T), and Humphrey 24-2 visual field mean deviation (HFA MD). Mean differences were statistically evaluated with ANOVA between Groups, and linear correlations were analysed with Pearson's test. At 6 months, significant differences between groups for all parameters were observed (ANOVA, p<0.01). In NC eyes, VA increased, PERG responses increased, VEP recordings improved and were significantly correlated with increases in HFA MD (p<0.01), and RNFL-T was unmodified or improved. In contrast, in NN eyes, VA, PERG, VEP responses, RNFL-T, and HFA MD were further worsened. Significant differences were still present at 9-month follow-up in the NN Group and after 3 months of OS-Citicoline wash-out in NC eyes. OS-Citicoline treatment induced neuroenhancement (improvement in RGCs function and neural conduction along visual pathways related to improvement of visual field defects) and neuroprotection (unmodified or improved RNFL morphological condition) in a human model of NAION involving fast RGCs degeneration. ClinicalTrials.gov NCT03758118.